Empowering your financial with ultimate financial companion / Arif Nasirudin Alawdin … [et al.] - Alawdin, Arif Nasirudin; Omar Hanafiah, Nur Atiqah Syahirah; Abas, Nur Alieya Natasya; Abdul Razzaq, Izzwan Ariff; Zuraini, Nur Izzati; Khairudin, Nur Athirah; Sabri, Nurbaity (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
In today's fast-paced financial landscape, managing personal finances efficiently remains a daunting challenge for many. Traditional methods often lead to errors, delays, and incomplete insights which hamper effective decision-making. This project proposed a groundbreaking innovation to revolutionize financial personal management and expert guidance through an integrated mobile application. An application combines users' bank accounts, allowing for automated cash flow control by synchronizing real-time bank transactions. Furthermore, it has a unique ability to scan receipts and automatically detect where they come from and which category to facilitate efficient record management and expense monitoring. An important feature of the application is its capacity to produce comprehensive financial statements, offering users a comprehensive overview of their financial situation. The inclusion of advanced ratio formulas and the option for expert consultations elevate users' ability to evaluate and optimize their financial health effectively. It also allows users to create transaction limit reminders to encourage smart spending habits. To augment users' financial knowledge, the application provides workshops and webinars on several aspects of financial planning. Customers also may access a carefully selected assortment of electronic books related to finance, such as budgeting, investing methods, and wealth management. This application is a breakthrough in financial management technology, providing users with a wide range of tools and resources to enhance their financial well-being.